ASN CORPORATE UNIVERSITY: TRANSFORMATION OF COMPETENCY DEVELOPMENT OF STATE CIVIL APPARATUS (ASN): ASN CORPORATE UNIVERSITY: TRANSFORMASI PENGEMBANGAN KOMPETENSI APARATUR SIPIL NEGARA (ASN) - Sumanti, Rati (Jurnal Transformasi Administrasi, 2025)
Competency development is very crucial in improving the performance of the State Civil Apparatus (ASN), not only is it important to provide quality guarantees for the public services that will be provided to the community, but competency development is also to create a work environment that is professional, efficient and adaptive to current developments. As the challenges and obstacles faced by government agencies become increasingly complex in the era of volatility, uncertainty, complexity, and ambiguity (VUCA), conventional competency development models alone are not enough to meet future needs. This article aims to explore the transformation that occurred in developing the competence of the ASN, especially through the implementation of the ASN Corporate University. This research uses a qualitative approach aimed at understanding the changes that have occurred in the development of ASN competencies in Indonesia. Data was collected through analysis of policy documents and literature reviews in the form of articles published by national journals related to the development of ASN competencies in Indonesia. The results of the analysis show that there are changes in performance effectiveness, cost implications and adaptability by implementing ASN Corporate University rather than conventional competency development. The findings of this article illustrate that the transformation through the ASN Corporate University has brought positive changes in increasing ASN competency, including increasing employee participation. The implication of the results of this research is the importance of continuing to encourage innovation and transformation in developing ASN competencies to support the achievement of national development goals.